Silent Anemia in Pregnancy - Reny Faristin Putri Arifin; Wildan Firmansyah (Jurnal Indonesia Sosial Teknologi, 2024)
Anaemia is a condition in which the number of red blood cells or the haemoglobin concentration within them is lower than normal. Thalassemia is a Mutation of the globin gene can cause changes in the globin chain, e.g. structural haemoglobinopathy or changes in the rate of synthesis or the production ability of certain globin chains. Epidemiological research in Indonesia found that the frequency of the beta thalassemia gene ranges from 3-10%. Case report of patient Mrs. T, 27 years old, HPHT: 01-10-2023, routine ANC examination every month, ANC examination results 18-19 weeks no complaints and laboratory examination results Hb 4.7. Patients with thalassemia beta major and intermediate need to be given regular transfusions and kept their hemoglobin levels above 10 mg/dl. All patients with homozygous thalassaemia should receive folic acid supplements.